Near Misses" Regarding Cataract Operation In Small Incision Cataract Surgery: How Do We Rectify Understanding And Documentation? - Pankaj Kumar Baranwal; Arunendu Shekar Thakur (Asian Journal of Medical Research, 2019)
Background: Aim: Near misses are widely reported   to the precursors of adverse events that highlight vulnerabilities and potentially unsafe areas of practice .The aim of this study was to see if a descriptive method of recording near misses was an appropriate method for use in an ophthalmic operating theatre and to quantify how many untoward events were recorded using this system related to the cataract surgery. Subjects and Methods: The study was wholly conducted in a operation theatre in the HIMS, Varanasi. The operation theatre staff assigned to the patient in their journey through the operating theatre was asked to note any untoward events. As, at present, there is no consensus definition of near misses in ophthalmology the staff recorded, in free text, any events that they considered to be a deviation from the normal routine in that theatre. Results: 250 cataract cases were randomly enrolled, 48 "deviations from normal routine" were described in 46 patients - that is, 19% of cases. All forms distributed to the staff were returned (100% response rate). The commonest abnormal events were intraoperative (35), with a lesser number being recorded preoperatively (13). When these events were further classified, it was thought that 13 could be classified as near misses. Once true adverse event was recorded during the study. Conclusion: The result suggest that experienced   staff in an ophthalmic theatre are a reliable source for collecting data regarding near misses. A consensus is now required to define near misses in ophthalmology and to devise a user friendly input system that can use these definitions to consistently record these potentially vital events.